EFFECTS OF FADAMA III PROJECT ON RURAL RICE FARMERS IN YOLA -NORTH LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA
The study assessed the effects of Fadama lll on rural rice farmers in Yola-North LGA of Adamawa State, Nigeria. The objectives are to; described the socio-economic characteristics of the respondents, Estimate the cost and returns of Fadama and non-Fadama participants, to assess the change in output and to assess the change in income among the respondents. One hundred and twenty four (124) respondents were selected from beneficiaries and non-beneficiaries of the project through multi stage and purposive random sampling. Structured questionnaire were used to obtained data on the Socio-economic characteristics, Cost and Returns, Change in output and Change in income. The data were analysed using Descriptive and inferential statistics. The findings reveals that majority of the respondents were males (71.4%) and married (69.6